Comparative LCA of different graphene production routes - Cossutta, Matteo; McKechnie, Jon; Pickering, Stephen J. (Royal Society of Chemistry, 2017)
This study is an LCA of three graphene production routes: electrochemical exfoliation of graphite rods, chemical oxidation and subsequent chemical or thermal reduction and chemical vapour deposition (CVD). Different processes for each route are analysed and their cradle-to-gate LCA is presented. A comparative LCA of the least impacting processes for each route is also presented showing that the chemical oxidation process followed by thermal reduction is the least impacting to produce large quantities of graphene when lab equipment is used to its full potential.